Imaging gradual neurodegeneration in a basal ganglia model disease. Issue 4 (23rd August 2019) - Hanssen, Henrike; Prasuhn, Jannik; Heldmann, Marcus; Diesta, Cid C.; Domingo, Aloysius; Göttlich, Martin; Blood, Anne J.; Rosales, Raymond L.; Jamora, Roland D. G.; Münte, Thomas F.; Klein, Christine; Brüggemann, Norbert
Abstract : Objective: X‐linked dystonia‐parkinsonism (XDP) is a neurodegenerative disease with adult onset dystonia and subsequent parkinsonism. Postmortem and imaging studies revealed remarkable striatal pathology, with a predominant involvement of the striosomal compartment in the early phase. Here, we aimed to disentangle sequential neurodegeneration in the striatum of XDP patients, provide evidence for preferential loss of distinct striatal areas in the early phase, and investigate whether iron accumulation is present. Methods: We used multimodal structural magnetic resonance imaging (voxel‐based morphometry and relaxometry) in 18 male XDP patients carrying a TAF1 mutation and 19 age‐matched male controls. Results: Voxel‐based relaxometry and morphometry revealed (1) a cluster in the anteromedial putamen showing high iron content and severe atrophy (−55%) and (2) a cluster with reduced relaxation rates as a marker for increased water levels and a lower degree of atrophy (−20%) in the dorsolateral putamen. Iron deposition correlated with the degree of atrophy (ρ = −0.585, p = 0.011) and disease duration (ρ = 0.632, p = 0.005) in the anteromedial putamen. In the dorsolateral putamen, sensorimotor putamen atrophy correlated with disease severity (ρ = −0.649, p = 0.004). Interpretation: This multimodal approach identified a patchy pattern of atrophy within the putamen. Atrophy is advanced and associated with iron accumulation in rostral regions of the striatum, whereas neurodegeneration is moderate and still ongoing in dorsolateral areas. Given the short disease duration and predominant dystonic phenotype, these results are well in line with early and preferential degeneration of striosome‐rich striatal areas in XDP. ANN NEUROL 2019;86:517–526